Effects of boron and vermicompost on growth, yield and nutrient content of Chilli (Capsicum annum L.) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
The effects of boron (B) and vermicompost (VC) on growth and yield of Chilli (Capsicum annum L.) and nutrient accumulation in its fruits was examined. The highest plant height (22 cm), leaf number per plant (73), leaf area (502.53 cm2/plant), dry weight (22.27g/plant), fruit length (8.97cm), fruit number per plant (6), fruit yield (11.76 g/plant) were recorded in B0.5 kg/ha + VC5 ton/ha at harvest. The results of growth and yield of Chilli varied significantly (p